2011
DOI: 10.1590/s0004-282x2011000600015
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal examination as a predictor of obstructive sleep apnea: pilot study of gag reflex and palatal reflex

Abstract: Obstructive sleep apnea (OSA) has high prevalence and may cause serious comorbities. The aim of this trial was to show if simple noninvasive methods such as gag reflex and palatal reflex are prospective multivariate assessments of predictor variables for OSA. Method: We evaluate gag reflex and palatal reflex, of fifty-five adult patients, and their subsequent overnight polysomnography. Results: Forty-one participants presented obstructive sleep apnea. The most relevant findings in our study were: [1] absence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Specifically, the investigators found evidence of a relationship between lower axonal density in soft palatal nerve fascicles and degree of swallowing dysfunction [32]. Similarly, Valbuza and colleagues [46] reported impaired palatal and gag reflexes in patients with moderate-severe OSAS. Collectively, the evidence suggests that palatal-pharyngeal injury may be due to repeated trauma and tissue stretching resulting from lowfrequency snoring vibrations.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, the investigators found evidence of a relationship between lower axonal density in soft palatal nerve fascicles and degree of swallowing dysfunction [32]. Similarly, Valbuza and colleagues [46] reported impaired palatal and gag reflexes in patients with moderate-severe OSAS. Collectively, the evidence suggests that palatal-pharyngeal injury may be due to repeated trauma and tissue stretching resulting from lowfrequency snoring vibrations.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies on swallowing in patients with OSA have reported that patients with OSA have impaired sensory and motor function of the pharyngeal structure, due to the low-frequency vibrations of habitual snoring and presence of abnormal signs of swallowing [ 23–37 , 39–42 ]. These factors are thought to be involved in the delay of the onset of swallowing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPAP may improve subclinical swallowing dysfunction in OSA (Okada et al, 2000). Palatal reflexes to tactile stimuli such as the gag reflex are diminished, particularly in severe OSA (Valbuza et al, 2011a). The extent to which these changes are caused by sensory impairments or efferent changes and whether or not they influence OSA severity remains unknown.…”
Section: Functionmentioning
confidence: 99%